Potential of an acoustic method for quantifying the activities of grazing cattle - Da Trindade, Júlio Kuhn; Carvalho, Paulo César de Faccio; Neves, Fabio Pereira; Pinto, Cassiano Eduardo; Gonda, Horacio Leandro; Nadin, Laura Beatriz; Correia, Luiz Henrique Silva (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the potential of an acoustic method for quantifying the duration of grazing, rumination, and other activities of beef heifers on natural pasture. To obtain sound recordings, heifers were fitted with a digital recorder and a microphone was mounted on the heifer’s forehead. The recordings were analyzed using audio software. Activities were discriminated, and their duration was quantified and compared with those obtained using a visual method. The acoustic method is efficient in quantifying the duration of grazing, rumination, and other activities of grazing cattle.